Pegylated Liposomal Doxorubicin, Docetaxel, and Trastuzumab as Neoadjuvant Treatment for HER2-Positive Breast Cancer Patients: A Phase II and Biomarker Study - Wang, Haoqi; Li, Yuntao; Qi, Yixin; Zhao, Erbao; Kong, Xiangshun; Yang, Chao; Yang, Qiqi; Zhang, Chengyuan; Liu, Yueping; Song, Zhenchuan (Frontiers in Oncology, 2022)
Background Combined neoadjuvant chemotherapy with trastuzumab and pertuzumab is the standard regimen for human epidermal growth receptor 2 (HER2)-positive breast cancer (BC). However, pertuzumab is not available because it is not on the market or covered by medicare in some regions or poor economy. Anthracyclines and taxanes are cornerstones in BC chemotherapy, and their combination contributes to satisfactory efficiency in neoadjuvant settings. Nonetheless, concomitant administration of trastuzumab and an anthracycline is generally avoided clinically due to cardiotoxicity. Pegylated liposomal doxorubicin (PLD) is less cardiotoxic compared with traditional anthracyclines. Here, we conducted this prospective study to evaluate the efficacy, safety, and potential biomarkers for PLD plus trastuzumab and docetaxel as neoadjuvant treatment in HER2-positive BC. Patients and Methods Patients with stage II or III HER2-positive BC were recruited in this multicenter, open-label, single-arm, phase II study. Eligible patients were given 6 cycles of PLD plus docetaxel and trastuzumab. Primary endpoint was total pathological complete response (tpCR, ypT0/is ypN0). Secondary endpoints were breast pathological complete response (bpCR, ypT0/is), objective response rate (ORR), operation rate, breast-conserving surgery rate, and safety. Metadherin (MTDH), glutaminyl-peptide cyclotransferase (QPCT), topoisomerase II alpha (TOP2A), programmed death ligand 1 (PD-L1), and tumor-infiltrating lymphocytes (TILs) were evaluated in BC tissues pre-neoadjuvant for potential biomarkers. Results Between March 2019 and February 2021, 54 patients were enrolled, 50 were included in the analysis, and 35 (70.0%) completed 6 cycles of neoadjuvant treatment. Forty-nine (98.0%) patients underwent surgery with a breast-conserving rate of 44.0%. The tpCR rate, bpCR rate, and ORR were 48.0% (95% CI, 33.7%–62.6%), 60.0% (95% CI, 45.2%–73.6%), and 84.0% (95% CI, 70.9%–92.8%), respectively. tpCR was associated with MTDH (p = 0.002) and QPCT (p = 0.036) expression but not with TOP2A (p = 0.75), PD-L1 (p = 0.155), or TILs (p = 0.76). Patients with HR-negative status were more likely to achieve bpCR compared with those with HR-positive status (76.2% vs. 48.3%, p = 0.047). Grade ≥3 adverse events occurred in 38.0% of patients. Left ventricular ejection fraction decline by ≥10% was reported in 18.0% of patients, and no patient experienced congestive heart failure. Conclusions PLD plus docetaxel and trastuzumab might be a potential neoadjuvant regimen for HER2-positive BC with a high tpCR rate and manageable tolerability. MTDH and QPCT are potential predictive markers for tpCR.